Determination and control of insect population for immature stage on Kuang rubber plantation / Nur Fitrah Abdul Rani - Abdul Rani, Nur Fitrah (Faculty of Plantation and Agrotechnology, 2018)
Modern agriculture mostly relies on chemical in order to control insect resulting in the deterioration and imbalance of the ecosystem in rubber plantation. Additionally, climate factors also have fraction towards ecosystem, hence, it affected on the diversity and distribution of insects. Insects diversity studies were conducted for four weeks of sampling period at rubber plantation to assess the population of insects. Insect were collected randomly by using two methods which is yellow sticky trap and yellow pan trap. Insects diversity at Kuang rubber plantation has been changing over the time which the increasing value of diversity is proportional to week sampling. The results were indicated the dominant insect by Diptera which is species of Agromyza spp. The factor that are contributed to the quantity and diversity of insect population on rubber plantation are depends on the climate factors such as temperature , rainfall and environment.